Performances and Egg Quality of Quail Offered Feed Containing Sterol from Katuk (Sauropus androgynus) and Mulberry (Morus alba) Leaf Meal - Hermana , Widya; Toharmat, Toto; Sumiati; Manalu, Wasmen (International Journal of Poultry Science, 2014)
Katuk (Sauropus androgynus) and mulberry (Morus alba) leaves meal contain cholesterol, campesterol, stigmasterol, sitosterol and 2-4alpha-methylsterol. These active substances were expected to increase nutrients metabolism in laying poultry including quail. Poultry in layer period have high nutrients requirement and mobilization. Usage of Katuk and mulberry leaves meal in the diet was expected to increase egg quality. Four dietary treatments and 5 replications of 15 quails of 6 weeks of age each, were allocated in a completely randomized design. Parameters observed were feed consumption, egg weight, quail day production and egg quality. The results showed that feed consumption and egg weight were not affected by the treatments, while egg production was significantly decreased by feeding the 10% mulberry leaf meal as well as the mixture of 5% Katuk and mulberry leaf meal (P < 0.05). Feeding 10% Katuk leaf meal did not affect the performances of the quail but the egg indicated the highest vitamin A and yolk colour score. It was concluded that 10% Katuk leaf meal could be fed to the laying quail to increase the egg quality without decreasing the production.